THE INFLUENCES OF CORPORATE SOCIAL RESPONSIBILITY COMMUNICATION VIA ONLINE MEDIA ON TRUST, ADVOCACY, AND BRAND EQUITY IN OIL BUSINESS AMONG THAI CONSUMERS - Meesuwan , Thunyalux; Vantamay, Nottakrit (Journal of MCU Nakhondhat, 2023)
The objectives of this research article were to: 1. corporate social responsibility communication via online media in various fields including 1) Trust 2) Advocacy 3) Brand Equity and 2) the influence of corporate social responsibility communication via online media in various fields including 1) Trust 2) Advocacy 3) Brand Equity is quantitative research using the survey research process the sample is Thai consumers. Multi-Stage Random Sampling was selected of 400 people. Methods used in the research were: online questionnaire. The statistics used for the analysis were frequency, percentage, mean and standard deviation, t-test, One-Way ANOVA and Multiple Regression Analysis (MRA) with a statistical significance level of 0.05. The research findings indicated that 1. Exposure to Corporate Social Responsibility Communication via Facebook the most, most of them are exposure to communicating corporate social responsibility through Facebook. Followed by Website, YouTube, Line, and Instagram. 2. The Influences of Corporate Social Responsibility Communication Via Online Media in Oil Business Among Thai Consumers. In various fields including 1) Trust, there are 3 channels, arranged as follows: (1) Facebook (2) YouTube and (3) Instagram 2) Advocacy, there are 3 channels, arranged as follows: (1) Facebook (2) Website and (3) Instagram 3) Brand Equity, there are 5 channels, arranged as follows: (1) Website (2) Facebook (3) YouTube (4) Line and (5) Instagram. The results of this research the results of this research can be used as a guideline for oil business conductors in choosing online media effectively. Moreover, it is useful for those who are interested in studying research related to the use of online media in communicating social responsibility.